Depression Among Nonfrail Old Men Is Associated With Reduced Physical Function and Functional Capacity After 9 Years Follow-up: The Health in Men Cohort Study. - Almeida, O.; Hankey, G.; Yeap, B.; Golledge, J.; Hill, Keith; Flicker, L. (2017)
BACKGROUND: Older adults with depression have increased risk of frailty and death. OBJECTIVE: To determine if history of depression hinders future physical and functional capacity. DESIGN, SETTING, AND PARTICIPANTS: Prospective longitudinal cohort study of 1148 men aged 70-87 years who were living in the Perth metropolitan community in 2001-2004 and completed a follow-up assessment of physical and functional capacity in 2011-2012. MAIN OUTCOME AND MEASURES: Outcomes were collected in 2011-2012 and included 4 measures of physical function (timed up-and-go, timed sit-to-stand, functional reach, and step test) and the assessment of basic (activities of daily living) and instrumental activities of daily living. We also collected information on depression and frailty [using the FRAIL (fatigue resistance ambulation illness, and loss of weight) scale] in 2001-2004 and 2011-2012. Frail men at the 2001-2004 were excluded from the analyses. RESULTS: Men with history of depression at the 2001-2004 assessment showed significantly worse performance than their counterparts in the timed sit-to-stand and step tests 9 years later. They also had approximately twice the risk of attaining the lowest decile of performance in both tests (analyses adjusted for age, education, and prevalent depressive symptoms). In addition, the adjusted risk ratio of impaired instrumental activities of daily living was 58% (95% confidence interval 15%, 116%) greater for men with than without history of past depression. These associations were particularly robust for men with current depression at the 2001-2004 assessment. CONCLUSIONS: Nonfrail older men with history of current or past depression showed greater impairment of physical and functional capacity 9 years later. Older men with history of depression may benefit from regular monitoring of physical and occupational function and should be targeted by preventive trials designed to improve function and decrease frailty.